2020
DOI: 10.1084/jem.20201738
|View full text |Cite
|
Sign up to set email alerts
|

Placental inflammasome signaling: Protection for mother and baby

Abstract: The second trimester of pregnancy is traditionally viewed as an immunosuppressive state. Megli et al. (https://doi.org/10.1084/jem.20200649) change this paradigm, showing that midgestation induces inflammasome signaling in placental trophoblasts to promote fetal and maternal antimicrobial defense. The placenta is thus a dynamic immunological organ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This complex catalyzes a cellular reaction that leads to the processing and maturation of two proinflammatory cytokines, the interleukin (IL)-1β and IL-18 [3,5]. Beside its proinflammatory role against immediate dangers [6], NLRP7 overexpression has been reported to function in an inflammasome-independent manner and exhibit antiinflammatory role by inhibiting IL-1β production [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This complex catalyzes a cellular reaction that leads to the processing and maturation of two proinflammatory cytokines, the interleukin (IL)-1β and IL-18 [3,5]. Beside its proinflammatory role against immediate dangers [6], NLRP7 overexpression has been reported to function in an inflammasome-independent manner and exhibit antiinflammatory role by inhibiting IL-1β production [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The first and third trimesters of human pregnancy are known to induce a strong physiological inflammation status (42). Recent studies showed that the second trimester of pregnancy also induces inflammasome signaling in placental trophoblasts to promote fetal and maternal antimicrobial defenses (43).…”
Section: Pregnancy/gestation Placental and Neonatal Inflammasomes During T Cruzi Infectionmentioning
confidence: 99%
“…Under certain conditions, the extrusion can occurs with neutrophil survival, a process termed as "vital NETosis". (Burgener & Schroder, 2020).…”
Section: Other Forms Of Programmed Necrosismentioning
confidence: 99%
“…These extracellular traps also contain antimicrobial proteins such as, MPO, NE, Proteinase 3 (PR3), Cathepsin G, Lysozyme and α-defensins representing a non-phagocytic mode of neutralize and degrade invading pathogens (Branzk & Papayannopoulos, 2013;Urban et al, 2009) and are able to stimulate the production of Interferon-α (IFN-α), a strong antiviral cytokine (Garcia-Romo et al, 2011). In the past 10 years, this form of PCD has been extensively studied to elucidate the sequence of its molecular events and its role in immune response, demonstrating that is actually one of the most specialized immune mechanism, which can be activated depending on microbe size and location, and as a strategy to control pathogens which are able to escape from neutrophil phagocytosis (reviewed in (Burgener & Schroder, 2020)). The effectiveness of this antimicrobial defense is evident in some pathogens such as Group A Streptococcus and Staphylococcus aureus , that produce nucleases and DNA binding proteins to impair NET formation and block NETosis as an active evasion mechanism (Storisteanu et al, 2017).…”
Section: Regulated Necrosis and Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation